A novel photosensitizer based on a ruthenium(ii) phenanthroline bis(perylenediimide) dyad: synthesis, generation of singlet oxygen and in vitro photodynamic therapy. (5th October 2018) - Aksakal, Nuray Esra; Kazan, Hasan Hüseyin; Eçik, Esra Tanrıverdi; Yuksel, Fatma
Abstract : In this study, a novel photosensitizer having two perylenediimide units and a phenanthroline ruthenium(ii ) coordination moiety (Ru-BP) has been developed for photodynamic therapy (PDT) of cancer cells. Abstract : In this study, a novel photosensitizer having two perylenediimide units and a phenanthroline ruthenium(ii ) coordination moiety (Ru-BP ) has been developed for photodynamic therapy (PDT) of cancer cells. This new compound was prepared via reactions of two newly designed molecules, namely, 5, 6, 12, 13-tetrakis(4-( tert -butyl)phenoxy)-2-(2, 6-diisopropylphenyl)-9-(4-hydroxyphenyl)anthra[2, 1, 9- def :6, 5, 10- d ′ e ′ f ′]diisoquinoline-1, 3, 8, 10(2 H, 9 H )-tetraone (P6 ) and a bis(2, 2′-bipyridyl)-(4, 7-dichlorophenanthroline)ruthenium(ii ) complex (7 ). The singlet oxygen production ofP6 andRu-BP was investigated by a chemical method using 1, 3-diphenylisobenzofurane as a trap molecule. Additionally, photodynamic therapy efficacy of the novelRu-BP complex andP6 was evaluated in vitro .Ru-BP significantly decreased the viability of human chronic myeloid leukemia cells under red light but not in the dark, pointing out that the complex, itself, was not cytotoxic and singlet oxygen formation was required for the initiation of cell death mechanisms. Thus, Ru-BP can be effectively used as a photosensitizer in photodynamic therapy, which makes the novelRu-BP a promising singlet oxygen generator for further biological applications.